A low energy consumption membrane electrode
By using a bubble-relieving functional mixture composed of aminofunctional metal oxides and perfluorosulfonic acid resin in the PEMWE catalytic layer, combined with a catalyst, a low-energy-consuming catalytic layer is formed, which solves the problem of increased electrolytic energy consumption caused by bubble adhesion in the catalytic layer. Achieve more efficient and long-lasting membrane electrode performance.
Patent Information
- Application Number
- CN202410399024.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-11-27
AI Technical Summary
The existing PEMWE catalytic layer is prone to bubble adhesion during the electrolysis process, resulting in an increase in electrolytic energy consumption, limiting the promotion and application of membrane electrodes.
A bubble-free functional mixture is used, consisting of amino-functionalized metal oxides and perfluorosulfonic acid resin, and combined with a catalyst, a low-energy-consuming catalytic layer is formed to improve the hydrophilicity and ionic conduction properties of the catalytic layer.
It effectively reduces the electrolytic energy consumption of the catalytic layer, improves the anti-bubbing performance, extends the service life, improves the proton conduction function, and reduces production costs.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
[0001] This application is a divisional application based on the application No. 202311586005.2 (the application date is 2023-11-27, and the name of the invention is a low-energy consumption catalytic layer and its preparation method). Technical Field
[0002] The invention relates to the technical field of water electrolysis catalysis, in particular to a low-energy consumption membrane electrode. Background Art
[0003] Proton membrane electrolysis (PEMWE) is recognized as a technology with good development prospects in the field of hydrogen production by water electrolysis. The electrolytic cell it uses has a compact structure, small size, and is conducive to rapid load changes. The electrolyzer has high efficiency, high gas purity, low energy consumption, and greatly improved safety and reliability. In addition, the PEMWE electrolyzer has a hydrogen production response time of less than 5s. Its fast dynamic response speed can perfectly match the intermittent and volatile nature of renewable energy generation, and is suitable for direct coupling of renewable energy generation such as wind and solar to produce hydrogen, becoming the focus of research and development in the field of green hydrogen production.
[0004] The membrane electrode is a key core component of PEMWE water electrolysis hydrogen production. It is crucial to the performance, efficiency and life of water electrolysis hydrogen production, and accounts for an increasing proportion of system costs as the scale of mass production expands. The membrane electrode is mainly composed of a proton exchange membrane, anode and cathode catalyst layers, anode and cathode gas diffusion layers, anode and cathode end plates, etc., and its structure is similar to that of a fuel cell. The three-phase interface and spatial configuration in the catalyst layer are usually formed by the catalyst layer slurry, among which perfluorosulfonic acid ion polymer (PFSA) is the key raw material commonly used for the catalyst layer slurry in PEMWE.
[0005] The cost of the membrane electrode accounts for about 70% of the total electrolyzer, and the catalyst layer in the membrane electrode is the main place for material transmission and electrochemical reaction in the entire water electrolyzer. Therefore, the performance of the catalyst layer plays a vital role in the operation of the entire membrane electrode performance electrolysis device. Electrons, oxygen and hydrogen ions will be produced when water is electrolyzed on the PEMWE catalyst layer; because the catalyst layer is closely attached to the ion membrane, the bubbles produced during the electrolysis process are very easy to adhere to the membrane surface and are difficult to release. A large number of bubbles gather on the membrane surface, blocking the current channel, reducing the effective electrolysis area of the membrane, and significantly increasing the local polarization effect, which in turn increases the cell pressure, ultimately leading to an increase in electrolysis energy consumption, limiting the promotion and application of PEMWE membrane electrodes.
[0006] In order to solve the above problems existing in the current PEMWE catalyst layer, a hydrophilic coating is introduced to construct a porous rough structure to reduce the adsorption of bubbles in the catalyst layer. The shortcomings of this method mainly include:
[0007] 1) The hydrophilic additives have poor compatibility with the perfluorosulfonic acid polymer, are unevenly distributed in the catalyst layer, and are prone to aggregation;
[0008] 2) Such added substances do not contain ionic groups, which will reduce the strength and conductivity of the catalytic layer;
[0009] 3) Small molecule additives will continue to degrade and be lost during long-term use and cannot provide long-term protection.
[0010] For example, Chinese patent CN111074296A discloses a bubble-repelling coating with ion conduction function and its preparation method; CN103556179A discloses a high current density perfluorinated ion exchange membrane modified by carbon nanotubes and its preparation method. However, the zirconium, hafnium or cerium oxides introduced into the above-mentioned coating or exchange membrane and the carbon nanotubes themselves do not have the proton conduction function, and the resulting composite catalyst layer structure will inevitably lose the ion conduction performance, resulting in an increase in the internal resistance of the membrane electrode catalyst layer and a decrease in the electrolysis efficiency. Summary of the invention
[0011] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a low-energy consumption membrane electrode, in which the catalytic layer includes a bubble-repelling functional mixture and a catalyst, wherein the bubble-repelling functional mixture is composed of amino-functionalized metal oxides and perfluorosulfonic acid resins, so that the catalytic layer has good hydrophilic contact angles and ion conductivity properties, thereby effectively controlling energy consumption.
[0012] In order to achieve the above technical effects, the present invention adopts the following technical solutions:
[0013] A low-energy consumption catalytic layer, comprising a gas bubble functional mixture and a catalyst, wherein the gas bubble functional mixture is composed of an amino-functionalized metal oxide (A) and a perfluorosulfonic acid resin (B), wherein the amino-functionalized metal oxide has a general structural formula as shown in formula (I),
[0014]
[0015] The perfluorosulfonic acid resin has a general structural formula as shown in formula (II),
[0016]
[0017] Preferably, in the bubble-repelling functional mixture, the molar fraction of the amino-functionalized metal oxide is 10-45%, and the molar fraction of the perfluorosulfonic acid resin is 55-90%; further preferably, the molar fraction of the amino-functionalized metal oxide is 15-30%, and the molar fraction of the perfluorosulfonic acid resin is 70-85%.
[0018] Preferably, the metal oxide MO in the amino-functionalized metal oxide is selected from one of zirconium dioxide (ZrO2), titanium dioxide (TiO2), aluminum oxide (Al2O3), iron oxide (Fe3O4) and cerium oxide (CeO2), and further preferably, the metal oxide MO is selected from ZrO2 or CeO2.
[0019] Preferably, the powder particle size of the metal oxide MO is 5 nm-5 μm, and more preferably, the powder particle size is 20 nm-1 μm.
[0020] Preferably, in the general structural formula of the perfluorosulfonic acid resin, m is an integer of 0-6, and n is an integer of 1-8; more preferably, m is an integer of 0-5, and n is an integer of 1-3.
[0021] Preferably, the ion exchange capacity (IEC) of the perfluorosulfonic acid resin is 0.5-3.5 mmol / g, preferably 0.9-2.0 mmol / g, more preferably 0.9-1.5 mmol / g; the number average molecular weight of the perfluorosulfonic acid resin is 100,000-800,000, preferably 300,000-700,000, more preferably 400,000-600,000.
[0022] Preferably, in the low-energy consumption catalytic layer, the mass ratio of the catalyst to the bubble-repelling functional mixture is (2-20):50; further preferably, the mass ratio of the catalyst to the bubble-repelling functional mixture is (5-10):50.
[0023] Preferably, the catalyst includes an anode catalyst and a cathode catalyst. When the catalyst is an anode catalyst, the low-energy consumption catalytic layer is an anode low-energy consumption catalytic layer. When the catalyst is a cathode catalyst, the low-energy consumption catalytic layer is a cathode low-energy consumption catalytic layer.
[0024] Preferably, the low energy consumption catalytic layer has a water contact angle of 15.2°-25.2°; the adhesion force measured in 250 g / L pure water with 3 μL air bubbles is in the range of 68-81 μN; at 0.1 A / cm 2 Under the condition that the flow rate of pure water is 300ml / min and the water temperature is controlled at 25°C, after the electrolytic cell is operated for 500h, the voltage increase range is 43.5-49.0μV / h; further preferably, the low energy consumption catalytic layer has a water contact angle of 15.2°; in 250g / L pure water, the adhesion range is 68μN measured with 3μL air bubbles; at 0.1A / cm 2 Under the condition of pure water flow rate of 300ml / min, water temperature controlled at 25℃, after the electrolytic cell ran for 500h, the voltage increase range was 43.5μV / h.
[0025] The present invention also provides a method for preparing the low-energy consumption catalyst layer, comprising the following steps:
[0026] S1. Preparation of amino-functionalized metal oxide (MO-NH2): The metal oxide is coated with polydopamine by co-precipitation reaction of dopamine and polyethyleneimine (PEI) in a solvent to graft the amino group (-NH2) onto MO. The product is washed and dried to obtain the MO-NH2 material. The reaction formula is as follows:
[0027]
[0028] S2. Preparation of perfluorosulfonic acid resin: The perfluorosulfonyl fluoride resin (PFSO2F) is soaked in alkali and acid successively to convert the -SO2F group into -SO3H. The product is washed and dried to obtain a perfluorosulfonic acid resin. The reaction formula is as follows:
[0029]
[0030] S3. The amino-functionalized metal oxide and perfluorosulfonic acid resin, i.e., a mixture of gas-dispersible functional groups in a water / alcohol mixed solvent to form a 2-15wt% dispersed solution;
[0031] S4. Preparation of low-energy catalytic layer: Add catalyst to the dispersed solution obtained in step S3 to obtain catalyst slurry, spray it onto a vacuum adsorbed transfer template after ultrasonic dispersion, and dry it under vacuum conditions at 80-140°C to obtain a low-energy catalytic layer.
[0032] Preferably, in step S1, the molar ratio of MO to dopamine is 1:(1-10), preferably 1:(1-3); the solvent is at least one of water, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, dichloromethane, acetone, dimethyl sulfoxide or ethyl acetate; the reaction temperature is 30-140°C, preferably 30-80°C; the reaction time is 8-48 hours, preferably 12-24 hours.
[0033] Preferably, in step S1, the number average molecular weight of polyethyleneimine is 10,000-100,000, preferably 30,000-60,000. The molar ratio of polyethyleneimine to dopamine is 1:(10-100), preferably 1:(50-70).
[0034] Preferably, in step S1 The structure is shown in the following formula (V):
[0035]
[0036] Preferably, the washing in step S2 is done with deionized water, and the drying is done at 55-65° C. for 18-36 hours.
[0037] Preferably, in step S3, the alcohol in the water / alcohol mixed solvent is ethanol or isopropanol, and the volume ratio of water to alcohol is (1-2):(8-9).
[0038] Preferably, in step S3, the molar fraction of the amino-functionalized metal oxide in the gas bubble functional mixture is 10-45%, and the molar fraction of the perfluorosulfonic acid resin in the gas bubble functional mixture is 55-90%; further preferably, the molar fraction of the amino-functionalized metal oxide in the gas bubble functional mixture is 15-30%, and the molar fraction of the perfluorosulfonic acid resin in the gas bubble functional mixture is 70-85%.
[0039] Preferably, in step S4, the ultrasonic dispersion time is 30-200 min, the transfer template is made of polytetrafluoroethylene, has a thickness of 3-5 mm, and is 2-5 cm longer and wider than the length and width of the proton exchange membrane. The transfer template is cleaned with anhydrous ethanol and stored dust-free before use.
[0040] Preferably, in step S4, the mass of the gas bubble functional mixture in the catalyst slurry accounts for 70wt% to 98wt% of the total mass of the gas bubble functional mixture and the catalyst. The catalyst is IrO2 or Pt / C.
[0041] Beneficial effects of the present invention:
[0042] 1. The catalyst layer structure of the low-energy consumption membrane electrode provided by the present invention introduces a bubble-repelling functional mixture, and both of the two in the mixture have hydrophilic properties, which solves the problem of poor compatibility between additives and perfluorosulfonic acid polymers in the prior art, and enables the catalyst layer to have a good hydrophilic contact angle, thereby improving its anti-foaming performance and effectively reducing the electrolysis energy consumption of the catalyst layer; the amino-functionalized metal oxide and perfluorosulfonic acid resin contained in the bubble-repelling functional mixture both have high molecular weights, which solves the problem of continuous loss of existing small molecule additives during use and effectively extends the service life of the low-energy consumption catalyst layer.
[0043] 2. The -NH2 group in component A of the bubble-repelling functional mixture provided by the present invention and the -SO3H group in polymer B can form -SO 3- ·····HN + SO 2- Acid-base ion pairs can cooperate with sulfonic acid groups to conduct protons, thereby improving the proton conduction function of the low-energy catalytic layer.
[0044] 3. The low-energy consumption catalyst layer preparation technology provided by the present invention is compatible with the traditional catalyst layer preparation process, which effectively improves the energy and equipment utilization rate and reduces the production cost. DETAILED DESCRIPTION
[0045] The present invention will be further described below in conjunction with the embodiments.
[0046] The reaction apparatus, polymer, reagents, and organic solvents involved in the following examples are all commercially available.
[0047] Embodiment 1:
[0048] A low-energy consumption catalytic layer comprises a gas bubble functional mixture and a catalyst, wherein the gas bubble functional mixture is composed of an amino-functionalized metal oxide (A) and a perfluorosulfonic acid resin (B), and the specific preparation steps are as follows:
[0049] S1. Metal oxide containing amino functional layer (MO-NH2): After cleaning a 100mL closed reactor and evacuating it and replacing it with high-purity nitrogen three times, 3.0g dopamine hydrochloride and 50mL Tris buffer solution were weighed, and the stirring device was turned on. After the stirring device was turned on, 1.0g ZrO2 particles with an average particle size of 50nm were added after they were completely dissolved, and the molar ratio of ZrO2 to dopamine hydrochloride was 1:2; the reaction was stirred at room temperature for 30min to modify the initially generated polydopamine on the surface of the ZrO2 particles, and then 12.7g PEI was weighed and dissolved in the mixed solution, and the molar ratio of PEI to dopamine hydrochloride was 1:50; after the addition was completed, a layer of polydopamine component was coated on ZrO2 through the co-precipitation reaction of dopamine and PEI at 80°C and mechanical stirring. After the reaction was completed for 12h, it was cooled to room temperature, repeatedly washed with deionized water three times, and dried at 60°C to obtain ZrO2 containing amino functional layer, which was recorded as product A1.
[0050] The reaction formula is as follows:
[0051]
[0052] S2. The PFSO2F resin was immersed in 15% KOH and 25wt% sulfuric acid solution at 80°C for 30h to complete ion exchange, and all -SO2F groups were converted into -SO3H. After repeated washing with deionized water three times, and drying at 60°C for 18h, the perfluorosulfonic acid ion polymer B1 was obtained. The reaction formula is as follows:
[0053]
[0054] S3. The bubble-repelling functional mixture (A1 mole fraction of 15.0%; polymer B1 mole fraction of 85.0%) was dissolved in a water / isopropanol (volume ratio of 2:8) mixed solvent, and stirred and dispersed uniformly to prepare a 12.0wt% dispersion solution;
[0055] S4. Then take two groups of 1.3mL dispersion solution (mass is about 2.6g) and add 25.0mg IrO2 and 7.5mg Pt / C catalyst respectively, and ultrasonicate for 100min to obtain anode catalyst slurry and cathode catalyst slurry; IrO2 is used as catalyst for the anode in the electrolytic water device, and Pt / C is used as catalyst for the cathode; the catalyst slurry is sprayed onto a polytetrafluoroethylene transfer template (thickness 5mm; length * width 5*5cm), and dried under vacuum conditions at 135℃ to obtain anode low-energy consumption catalyst layer and cathode low-energy consumption catalyst layer. The loading equivalents of IrO2 and Pt / C in the catalyst layer are 1.0mg / cm 2 and 0.5mg / cm 2 .
[0056] Among them, in polyethyleneimine (PEI), the number average molecular weight is 40,000; in PFSO2F resin, x=4, y=1; m=1, n=2, the number average molecular weight is 400,000, and the molar equivalent E w =900g / mol.
[0057] Embodiment 2:
[0058] A low-energy consumption catalytic layer, the preparation method is different from that of Example 1 in that: the number average molecular weight of PEI is 50,000, and the co-deposition reaction of dopamine and PEI is extended to 24 hours. In addition, the molar fraction of product A1 in the mixed product is increased to 25.0%; the molar fraction of polymer B1 accounts for 75.0%.
[0059] Embodiment 3:
[0060] A low-energy consumption catalytic layer, the preparation method of which differs from that of Example 1 in that CeO2 is used instead of ZrO2 to prepare the metal oxide of the amino functional layer, and in step S3, the molar fraction of A1 in the bubble-repelling functional mixture is increased to 18.0%.
[0061] Embodiment 4:
[0062] A low energy consumption catalyst layer, the preparation method is different from that of Example 1 in that: PFSO2F resin (x = 4, y = 1; m = 0, n = 2, number average molecular weight of 400,000, molar equivalent E w =800 g / mol) to prepare perfluorosulfonic acid ionomer B2. In addition, in step S3, the molar fraction of A1 in the bubble-repelling functional mixture is increased to 20.0%.
[0063] Embodiment 5:
[0064] A low energy consumption catalyst layer, the preparation method is different from that of Example 1 in that: PFSO2F resin (x = 4, y = 1; m = 0, n = 2, number average molecular weight of 400,000, molar equivalent E w=689 g / mol) to prepare perfluorosulfonic acid ion polymer B3, the molar fraction of A1 in the bubble-repelling functional mixture is 30.0%, and the molar fraction of B3 is 70.0%.
[0065] Comparative Example 1:
[0066] A water electrolysis catalyst layer, the preparation method is basically the same as that in Case 1, the only difference being that only perfluorosulfonic acid polymer B1 is used to prepare the catalyst slurry, and the resulting catalyst layer structure does not contain the amino-functionalized metal oxide A component.
[0067] In order to further illustrate the beneficial effects achieved by the embodiments of the present invention and various cases, the catalytic layers obtained in the embodiments and comparative examples were prepared into electrolytic membrane electrodes to test the water electrolysis performance.
[0068] It should be noted that the detection instruments and detection reagents involved below are all commercially available, and the detection methods used are searchable existing technologies.
[0069] The steps for preparing the membrane electrode are as follows:
[0070] 1) The polymer B1 in Example 1 was dissolved in a water / isopropanol (volume ratio of 2:8) mixed solvent, and a 12.0 wt% mixed solution was prepared after stirring and dispersing evenly to obtain a perfluorosulfonic acid ion polymer membrane solution, and then the solution was cast on a glass plate, pre-dried at 80° C., and then placed in an oven at 145° C. for 90 minutes. The membrane was removed and demolded to obtain a 20 μm perfluorosulfonic acid proton exchange membrane with an IEC of 1.10 mmol / g.
[0071] 2) The catalytic layers prepared in Examples 1 to 5 and Comparative Example 1 are loaded on a transfer template, and the transfer templates carrying the anode and cathode catalytic layers are respectively fixed on both sides of a proton exchange membrane (thickness 5 mm; length * width 3 * 3 cm), aligned up and down and well matched, and subjected to hot pressing treatment with a press. The pressure of the press is 1.0 MPa, the hot pressing temperature is 135°C, and the duration is 70 s. The press is opened, the transfer template is removed, and finally the sample is placed in a vacuum drying oven at 100°C for 2 h. After being taken out, a membrane electrode is obtained.
[0072] The membrane electrode was assembled into a water electrolysis cell. The specific steps are as follows: the anode current collector, anode gas diffusion layer, membrane electrode, cathode gas diffusion layer, and cathode current collector were assembled into a water electrolysis cell in sequence. The cathode porous diffusion layer used Toray carbon paper, and the anode diffusion layer used platinum-coated porous titanium. During the test, the flow rate of pure water was 300ml / min, the water temperature was controlled at 80℃, the stability test used a constant current test method, and the purity of hydrogen on the cathode side and oxygen on the anode side was detected by gas chromatograph.
[0073] Membrane electrode durability test:
[0074] At 0.1A / cm 2 Under the conditions of pure water flow rate of 300 ml / min and water temperature controlled at 25 °C, the stability of the membrane electrode samples was evaluated and the voltage increase rate was monitored after the electrolytic cell was operated for 500 h.
[0075] Titration of ion exchange capacity (IEC): Accurately weigh a certain weight of the dry target product, and then use a 1M NaCl aqueous solution for ion exchange for more than 12 hours. Collect the ion exchange solution, use phenolphthalein as an indicator, and titrate with 0.1M NaOH standard solution until the solution turns pink. The ion exchange capacity (IEC) value of the target product can be calculated according to the following formula:
[0076] IEC=(V NaOH ×C NaOH ) / m formula (V)
[0077] In formula (V): V NaOH ——The volume of NaOH standard solution consumed, mL; C NaOH ——molar concentration of NaOH standard solution, mmol / mL; m——mass of dry target product, g.
[0078] Adhesion was measured using 3 μL air bubbles in 250 g / L pure water.
[0079] The roughness Ra value of the catalyst layer (3*3 cm) of the membrane electrode was tested using an atomic force microscope (Park NX20).
[0080] The test results are shown in Table 1.
[0081] Table 1 Performance test results
[0082]
[0083]
[0084] Note: The current density @1.75V (or current density @2.0V) in the table refers to the current density at 1.75V (or 2.0V).
[0085] From the comparison between Examples 1-5 and Comparative Example 1, it can be seen that the bubble-repelling functional mixture introduced into the electrolytic water catalyst layer structure of the present invention can effectively reduce the adhesion of bubbles, control the total amount of bubble adhesion, and thus effectively control the voltage increase. The voltage increase of Examples 1-5 after 500 hours is only 43.5-49.0 μV / h; In addition, the contact angle of Examples 1-5 is 15.2-25.1°C, thereby giving the catalyst layer excellent hydrophilicity, significantly improving the current density, and improving the purity of oxygen on the anode side and the purity of hydrogen on the cathode side. In addition, the voltage increase of the catalyst layer is small after running in the membrane electrode for 500 hours, showing the characteristics of low energy consumption.
Claims
1. A low energy consumption membrane electrode, characterized in that: Prepared by the following steps: 1). Dissolve the perfluorosulfonic acid ion polymer in a water / isopropanol mixed solvent, stir and disperse evenly to prepare a 12.0wt% mixed solution to prepare a perfluorosulfonic acid ion polymer membrane liquid, then cast the perfluorosulfonic acid ion polymer membrane liquid on a glass plate, pre-dry at 80°C, place in an oven at 145°C for 90 minutes, take out and demold, and prepare a 20μm perfluorosulfonic acid proton exchange membrane; 2). Load the low-energy consumption catalyst layer on the transfer template, fix the transfer templates loaded with the anode catalyst layer and the cathode catalyst layer on both sides of the perfluorosulfonic acid proton exchange membrane, align and match well, and perform hot pressing with a press. The pressure of the press is 1.0 MPa, the hot pressing temperature is 135°C, and the duration is 70s. Open the press, remove the transfer template, and finally place the sample in a vacuum drying oven at 100°C for 2h. After taking it out, a low-energy consumption membrane electrode is obtained. In step 1), the preparation method of the perfluorosulfonic acid ionomer is as follows: the perfluorosulfonyl fluoride resin is soaked in alkali and acid successively to convert the -SO2F group into -SO3H, and the product is obtained after washing and drying; In step 2), the low energy consumption catalytic layer includes a gas bubble functional mixture and a catalyst, the catalyst is IrO2 or Pt / C, and the gas bubble functional mixture is composed of an amino functionalized metal oxide and a perfluorosulfonic acid resin. Wherein, the amino-functionalized metal oxide has a general structural formula as shown in formula (I), Formula (I); The perfluorosulfonic acid resin has a general structural formula as shown in formula (II), Formula (II); The preparation method of amino-functionalized metal oxide is as follows: In a solvent, polydopamine is coated on a metal oxide by a co-precipitation reaction of dopamine and polyethyleneimine, so that MO is grafted with amino groups. The product is washed and dried to obtain MO-NH2 material. The reaction formula is as follows: Formula (III); In the bubble-repelling functional mixture, the molar fraction of the amino-functionalized metal oxide accounts for 10-45%, and the molar fraction of the perfluorosulfonic acid resin accounts for 55-90%; The surface roughness of the low-energy consumption catalytic layer measured within a range of 3cm*3cm is in the range of 160nm-168nm; The metal oxide in the amino-functionalized metal oxide is selected from one of zirconium dioxide, titanium dioxide, aluminum oxide, iron oxide and cerium oxide; The particle size of the metal oxide powder is 5nm-5μm; In the general structural formula of the perfluorosulfonic acid resin, m is an integer of 0-6, and n is an integer of 1-8; The ion exchange capacity of the perfluorosulfonic acid resin is 0.5-3.5mmol / g, and the number average molecular weight of the perfluorosulfonic acid resin is 100,000-800,000; The catalyst includes an anode catalyst and a cathode catalyst. When the catalyst is an anode catalyst, the low-energy consumption catalyst layer is the anode catalyst layer. When the catalyst is a cathode catalyst, the low-energy consumption catalyst layer is the cathode catalyst layer.
2. The low energy consumption membrane electrode according to claim 1, characterized in that: In the bubble-repelling functional mixture, the molar fraction of the amino-functionalized metal oxide accounts for 15-30%, and the molar fraction of the perfluorosulfonic acid resin accounts for 70-85%.
3. The low energy consumption membrane electrode according to claim 1, characterized in that: The metal oxide MO in the amino-functionalized metal oxide is selected from ZrO2 or CeO2; The powder particle size of the metal oxide MO is 20nm-1μm.
4. The low energy consumption membrane electrode according to claim 1, characterized in that: In the general structural formula of the perfluorosulfonic acid resin, m is an integer of 0-5, and n is an integer of 1-3; The ion exchange capacity of the perfluorosulfonic acid resin is 0.9-2.0 mmol / g; the number average molecular weight of the perfluorosulfonic acid resin is 300,000-700,000.
5. The low energy consumption membrane electrode according to claim 4, characterized in that: The ion exchange capacity of the perfluorosulfonic acid resin is 0.9-1.5 mmol / g; the number average molecular weight of the perfluorosulfonic acid resin is 400,000-600,000.
6. The low energy consumption membrane electrode according to claim 1, characterized in that: In the low-energy consumption catalytic layer, the mass ratio of the catalyst to the bubble-repelling functional mixture is (2-20):
50.
7. The low energy consumption membrane electrode according to claim 6, characterized in that: In the low-energy consumption catalytic layer, the mass ratio of the catalyst to the bubble-repelling functional mixture is (5-10):
50.
8. The low energy consumption membrane electrode according to claim 1, characterized in that: The low energy consumption catalyst layer is prepared by the following steps: S1. Preparation of amino-functionalized metal oxides: metal oxides are coated with polydopamine by co-precipitation reaction of dopamine and polyethyleneimine in a solvent to graft amino groups onto MO. The product is washed and dried to obtain MO-NH2 material. The reaction formula is as follows: Formula (III); S2. Preparation of perfluorosulfonic acid resin: The perfluorosulfonyl fluoride resin is soaked in alkali and acid successively to convert the -SO2F group into -SO3H. The product is washed and dried to obtain a perfluorosulfonic acid resin. The reaction formula is as follows: Formula (IV); S3. The amino-functionalized metal oxide and perfluorosulfonic acid resin, namely, a mixture of gas-dispersing functional groups in a water / alcohol mixed solvent to form a 2-15wt% dispersed solution; S4. Preparation of low-energy catalytic layer: Add catalyst to the dispersed solution obtained in step S3 to obtain catalyst slurry, spray it onto a vacuum adsorbed transfer template after ultrasonic dispersion, and dry it under vacuum conditions at 80-140°C to obtain a low-energy catalytic layer.
9. The low energy consumption membrane electrode according to claim 8, characterized in that: In step S1, the molar ratio of MO to dopamine is 1:(1-10); the solvent is at least one of water, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, dichloromethane, acetone, dimethyl sulfoxide or ethyl acetate; the reaction temperature is 30-140° C.; the reaction time is 8-48 hours; The number average molecular weight of polyethyleneimine is 10,000-100,000; the molar ratio of polyethyleneimine to dopamine is 1: (10-100).
10. The low energy consumption membrane electrode according to claim 9, characterized in that: In step S1, the reaction temperature is 30-80°C; the reaction time is 12-24 hours; The number average molecular weight of polyethyleneimine is 30,000-60,000; the molar ratio of polyethyleneimine to dopamine is 1: (50-70).
11. The low energy consumption membrane electrode according to claim 8, characterized in that: In step S2, the washing is performed with deionized water, and the drying is performed at 55-65° C. for 18-36 hours.
12. The low energy consumption membrane electrode according to claim 8, characterized in that: In step S3, the alcohol in the water / alcohol mixed solvent is ethanol or isopropanol, and the volume ratio of water to alcohol is (1-2):(8-9); The molar fraction of the amino-functionalized metal oxide in the gas bubble functional mixture is 15-30%, and the molar fraction of the perfluorosulfonic acid resin in the gas bubble functional mixture is 70-85%.
13. The low energy consumption membrane electrode according to claim 8, characterized in that: In step S4, the duration of ultrasonic dispersion is 30-200 min, the transfer template is made of polytetrafluoroethylene, has a thickness of 3-5 mm, and the length and width are 2-5 cm larger than the length and width of the proton exchange membrane; The mass of the gas bubble repelling functional mixture in the catalyst slurry accounts for 70wt% to 98wt% of the total mass of the gas bubble repelling functional mixture and the catalyst.
Citation Information
Patent Citations
Carbon-nanotube-modified high-current-density perfluorinated ion exchange membrane and preparation method thereof
CN103556179A
Bubble adhesion preventing coating with ion conduction function and preparation method thereof
CN111074296A
Perfluorinated bipolar membrane and preparation method thereof
CN116036889A